3D printing goes greener: Study of the properties of post-consumer recycled polymers for the manufacturing of engineering components. (December 2020) - Pinho, Ana C.; Amaro, Ana M.; Piedade, Ana P.
Graphical abstract: Highlights: PLA and ABS were printed from post-consumer recycled waste. Chain scission caused by mechanical recycling influences the properties of PLA. Smoother surfaces are obtained in the printed parts from recycled filament. The recycled polymers can be reused for engineering components. Abstract: This study concerns the evaluation of several properties/characteristics of 3D printed poly(lactic acid) (PLA) polymer and acrylonitrile–butadienestyrene (ABS) copolymer, recycled from food packages and car dashboards, respectively. The aim is to evaluate the potential of recycled polymers that are recovered from solid polymer waste (SPW) to be reused for functional components/parts for add-value applications. The study compared the performance of the recycled material with the obtained from the 3D printing of virgin polymer. The characterization was made considering the chemical, thermal and mechanical properties as well as surface roughness and wettability. Although the thermal characterization did not indicate significant variations between recycled and virgin material, the mechanical recycling process induced some chain scission in PLA. Consequently, the semi-crystalline polymer revealed losses of 33% both in tensile stress and flexural strength. On the contrary, recycled ABS did not show changes in the mechanical properties of the printed specimens. Both recycled polymers produced smoother surfaces with a decrease of the mean surface roughness between 55% and 65%. Considering the properties required by manufacturers of food containers and car dashboards, this study indicates that recycled materials can be reused for the same applications.